Analysis of Public Service Center Service Innovation in Gresik Regency as a Health and Emergency Service - Irwanto, Bian Shabri Putri; Irwanto, Adella Saninah Putri; Mulia, Shinta Arta; Dwiyanti, Endang; Arfiani, Novi Dian (Universitas Nahdlatul Ulama Surabaya, 2023)
In the realm of public service innovation, one significant government initiative is the establishment of Public Service Centers (PSCs). This qualitative-descriptive research is conducted at the Gresik PSC and the East Java Health Office. PSC 119 Gresik operates as an emergency service under the Health Office's jurisdiction, catering to the community's urgent needs. While the Gresik PSC has shown successful implementation, encompassing community outreach, emergency response tasks, and reporting to the Health Office, it faces challenges. Notably, the Gresik PSC receives only 70 calls, a figure deemed suboptimal compared to the local population. Hindrances include the non-readiness of call center workers during emergencies, inadequate community awareness about PSC, and reports still being directed to three different agencies. To enhance the efficiency of Gresik PSC, recommendations include training call center operators to enhance communication tools and skills, cross-sector collaboration, routine monitoring, and evaluation every 3-6 months on a unified application or report, and intensified community outreach through social and print media.